Perlindungan Hukum Terhadap Konsumen Atas Jual Beli Non-Fungible Token (NFT) Melalui Smart Contract - Paramhamsa Yogananda, Gede; Rasmadi Arsha Putra, I Putu (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The rapid development of information technology has triggered changes towards digitization in all areas of life, one of which is in the field of trade. Digital platforms are now increasingly in demand by the public because of their practical, efficient and fast nature. One form of digital asset that has become popular in recent years is the Non-Fungible Token (NFT). With Non-Fungible Token (NFT) trading, of course there is a buying and selling process and the relationship between consumers and producers. This study aims to describe and analyze consumer protection for trade in copyrighted works in the form of Non-Fungible Tokens (NFT) through smart contracts. This research is a normative juridical research which is descriptive analytical with the statutory approach and conceptual approach. Secondary data sources in the form of primary, secondary and tertiary legal materials were collected using library research techniques. This study found that Non-Fungible Tokens (NFT) can raise legal issues because there is no comprehensive regulation governing Non-Fungible Tokens (NFT) both in terms of understanding, implementation and supervision, then consumers are not given legal protection in Non-Fungible transactions. Fungible Token (NFT) with smart contracts, the rights of consumers are not guaranteed in Non-Fungible Token (NFT) transactions and there is no regulation of the extent of seller's obligations as a producer in fulfilling legal protection for consumers. This threatens consumer rights and there is a need for clear and comprehensive regulations on Non-Fungible Token (NFT) transactions, to support a market that has begun to advance with the development of information technology.